Disparities in global COVID-19 vaccination rates & allocation of resources to countries in need. (August 2021) - Sen-Crowe, Brendon; McKenney, Mark; Elkbuli, Adel
Abstract: As of July 20th, 2021, over 191 million confirmed COVID-related cases and 4.1 million COVID-related deaths have been documented across the globe. Vaccines were initially prioritized in healthcare workers (HCWs) and elderly populations to provide protection to high-risk individuals. However, despite the intra-and-international distribution of COVID-19 vaccines, there is considerable variability in the vaccination rates observed worldwide. For example, the United Arab Emirates reported 166 vaccine doses/100 population, whereas most of the countries in Africa have administered <10 doses/100 population. The inadequate supply of vaccinations in addition to the lack of swift distribution/reallocation of vaccines that arrived likely contribute to the low vaccination rates observed in Africa. The US and many countries in Europe began administering vaccines in December 2020, whereas the majority of countries in Africa began administering vaccines in March 2021. In order to mitigate COVID-related deaths, we recommend that countries join in the efforts of allocating COVID vaccines to countries in need. In addition, we recommend for the partial vaccination of a larger proportion of high-risk population as opposed to fully vaccinating half the amount. However, adequate supply of vaccines may be of limited use if not distributed in a time-sensitive manner. We recommend for the implementation of targeted and cost-effective vaccine allocation and distribution strategies in order to increase vaccination rates, reserve healthcare systems resources and avoid any preventable deaths associated with COVID-19 infections.